2012
DOI: 10.1093/brain/aws186
|View full text |Cite
|
Sign up to set email alerts
|

Mapping motor representations in the human cerebellum

Abstract: The cerebellum is a major motor structure. However, in humans, its efferent topographical organization remains controversial and indirectly inferred from neuroimaging and animal studies. Even central questions such as 'Can we evoke limb movements by stimulating the cerebellar cortex?' have no clear answer. To address this issue, we electrically stimulated the posterior cerebellum of 20 human patients undergoing surgery for tumours located outside this structure (e.g. pineal gland, quadrigeminal plate). Stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
124
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(138 citation statements)
references
References 103 publications
10
124
4
Order By: Relevance
“…45,56,66 Hence, attributing activity in VI and VIIb solely to cognitive function may be an over simplification. 70 Indeed, direct electrical stimulation of lobules VI and VIIb elicits electromyogram activity in the hand and arm, 47 somatotopic organization has been demonstrated in lobule VI, 63 activity in lobule VIIb scales with the rate of force production, 69 and lesions to lobule VII negatively impact multisensory integration. 12 The differences in complexity of experimental tasks may explain the differences between a functional sub-region interpretation and a multisensory interpretation of cerebellar function.…”
Section: Discussionmentioning
confidence: 99%
“…45,56,66 Hence, attributing activity in VI and VIIb solely to cognitive function may be an over simplification. 70 Indeed, direct electrical stimulation of lobules VI and VIIb elicits electromyogram activity in the hand and arm, 47 somatotopic organization has been demonstrated in lobule VI, 63 activity in lobule VIIb scales with the rate of force production, 69 and lesions to lobule VII negatively impact multisensory integration. 12 The differences in complexity of experimental tasks may explain the differences between a functional sub-region interpretation and a multisensory interpretation of cerebellar function.…”
Section: Discussionmentioning
confidence: 99%
“…The inferior cerebellum is routinely recruited during motor tasks [68], [69]. Neurophysiological studies have shown electrical stimulation in this region evokes limb movements [68] and neuroimaging studies have demonstrated grey matter correlates with upper extremity function [69].…”
Section: Discussionmentioning
confidence: 99%
“…The collected signals were differentially amplified with a gain of 1,000-10,000 to fall within a ±5 V range, sampled at 10 kHz, filtered in a 30-300 Hz frequency band, and stored. For the purpose of computing motor latencies, EMG signals were further processed offline, as described in a previous paper (40). In brief, the envelope of the surface EMG was estimated by a scheme of demodulation, smoothing, and relinearization (41).…”
Section: Methodsmentioning
confidence: 99%